2020
DOI: 10.1038/s41598-020-75380-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-formed compositional superlattices triggered by cation orderings in m-plane Al1−xInxN on GaN

Abstract: Immiscible semiconductors are of premier importance since the source of lighting has been replaced by white light-emitting-diodes (LEDs) composed of thermodynamically immiscible InxGa1−xN blue LEDs and yellow phosphors. For realizing versatile deep-ultraviolet to near-infrared light-emitters, Al1−xInxN alloys are one of the desirable candidates. Here we exemplify the appearance and self-formation sequence of compositional superlattices in compressively strained m-plane Al1−xInxN films. On each terrace of atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Last but not least, the structural quality of thick nonpolar (101̅0) InAlN layers grown on bulk GaN has been studied. Severe composition instability and cation ordering process were reported to take place in order to mitigate the lattice mismatch along the [0001] direction . Note that degradation of the InAlN quality was also reported earlier for thick c -plane InAlN layers grown by MOVPE …”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Last but not least, the structural quality of thick nonpolar (101̅0) InAlN layers grown on bulk GaN has been studied. Severe composition instability and cation ordering process were reported to take place in order to mitigate the lattice mismatch along the [0001] direction . Note that degradation of the InAlN quality was also reported earlier for thick c -plane InAlN layers grown by MOVPE …”
Section: Introductionsupporting
confidence: 61%
“…Fundamental property studies as well as device demonstrations are reported. However, despite numerous studies on nonpolar and semipolar structures, there has been only a very limited number of them presenting InAlN grown on non- c -plane substrate orientations. Moreover, all of these studies describe layers and structures grown by metal–organic vapor-phase epitaxy (MOVPE) with no studies on semipolar or nonpolar InAlN layers grown by plasma-assisted molecular beam epitaxy (PAMBE). Therefore, it is very important to undertake experimental efforts toward a comprehensive understanding of InAlN growth mechanisms and controlling the resulting layer properties on non- c -plane GaN substrates using PAMBE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…layers can be formed on the fully relaxed semipolar GaInN layers, they will become highly promising structural components for long-wavelength visible GaN LDs. On the other hand, although some researchers have reported the growth of nonpolar [7,8,[24][25][26][27] and semipolar [26][27][28][29] AlInN layers, there have been no reports focusing on the growth of thick and flat-surface AlInN epitaxial layers with high-InN mole fraction. Therefore, in this study, we attempted to grow AlInN layers with submicrometer thicknesses and high-InN mole fractions using a fully relaxed semipolar GaInN template and to evaluate their crystal qualities including the surface flatness.…”
mentioning
confidence: 99%